Education of Patients With Atrial Fibrillation and Evaluation of the Efficacy of a Mobile Virtual Patient Environment: Protocol for a Multicenter Pseudorandomized Controlled Trial - Antoniou, P.; Dafli, E.; Giannakoulas, G.; Igimbayeva, G.; Visternichan, O.; Kyselov, S. M.; Lykhasenko, I. V.; Lashkul, D. A.; Nadareishvili, I.; Tabagari, S.; Bamidis, P. D.; Кисельов, Сергій Михайлович; et al. (My University, 2024)
Background: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia and is a leading cause of mortality and morbidity. Patient knowledge about AF and its management is paramount but often limited. Patients need to be appropriately informed about treatment options, medicinal adherence, and potential consequences of nonadherence, while also understanding treatment goals and expectations from it. Mobile health apps have experienced an explosion both in their availability and acceptance as “soft interventions” for patient engagement and education; however, the prolific nature of such solutions revealed a gap in the evidence base regarding their efficacy and impact. Virtual patients (VPs), interactive computer simulations, have been used as learning activities in modern health care education. VPs demonstrably improved cognitive and behavioral skills; hence, they have been effectively implemented across undergraduate and postgraduate curricula. However, their application in patient education has been rather limited so far. Objective: This work aims to implement and evaluate the efficacy of a mobile-deployed VP regimen for the education and engagement of patients with AF on crucial topics regarding their condition. A mobile VP app is being developed with the goal of each VP being a simple scenario with a set goal and very specific messages and will be subsequently attempted and evaluated. Methods: A mobile VP player app is being developed so as to be used for the design of 3 educational scenarios for AF management. A pseudorandomized controlled trial for the efficacy of VPs is planned to be executed at 3 sites in Greece, Ukraine, and Kazakhstan for patients with AF. The Welch t test will be used to demonstrate the performance of patients’ evaluation of the VP experience. Results: Our study is at the development stage. A preliminary study regarding the system’s development and feasibility was initiated in December 2022. The results of our study are expected to be available in 2024 or when the needed sample size is achieved. Conclusions: This study aims to evaluate and demonstrate the first significant evidence for the value of VP resources in outreach and training endeavors for empowering and patients with AF and fostering healthy habits among them.
Keywords: atrial fibrillation; virtual patient; scenario based learning; technology enhanced learning; mHealth; mobile health; patient engagement; patient education; cardiac arrhythmia; mortality; mobile application; mobile app; health education; randomized control trial; cardiology; cardiac; heart; Greece; Ukraine; Kazakhstan; clinical decision support systems; CDSS; virtual patient scenario; myocardial infarction; arrhythmia; stroke